2007
DOI: 10.1063/1.2799175
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of suprathermal ions from a colloidal microjet target containing SnO2 nanoparticles by using double laser pulses

Abstract: We have demonstrated suppression of suprathermal ions from a colloidal microjet target plasma containing tin-dioxide (SnO2) nanoparticles irradiated by double laser pulses. We observed a significant decrease of the tin and oxygen ion signals in the charged-state-separated energy spectra when double laser pulses were irradiated. The peak energy of the singly ionized tin ions decreased from 9to3keV when a preplasma was produced. The decrease in the ion energy, considered as debris suppression, is attributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…The Sn-3d intensities linearly increased with the increase of the laser pulses as expected. They represent similar values each other regardless of the irradiation modes, which showed a contrast to the ionic debris that was well suppressed by the double pulse irradiation [9]. These are unexpected results, indicating that ionic debris amount was very limited among the deposited debris amount.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The Sn-3d intensities linearly increased with the increase of the laser pulses as expected. They represent similar values each other regardless of the irradiation modes, which showed a contrast to the ionic debris that was well suppressed by the double pulse irradiation [9]. These are unexpected results, indicating that ionic debris amount was very limited among the deposited debris amount.…”
Section: Introductionsupporting
confidence: 72%
“…As a result, the EUV conversion efficiency of 1.2% at 13.5 nm was achieved [8], which was almost equal to that of using a planar tin target. By employing the double pulse irradiation, the kinetic energy and intensity of emitted ionic debris were both decreased [9]. This observation was important to construct practical EUV sources, since low-energy ionic debris could be screened out by using a static electric-and/or magneticfield shielding [10].…”
Section: Introductionmentioning
confidence: 98%
“…22 It was also shown that LPPs exhibit preferential emission close to target normal; the energy of the ions emitted close to the target normal were also higher than that of ions emitted at larger angles. 23 Higashiguchi et al 24 demonstrated suppression of suprathermal ions from a colloidal microjet target plasma containing tin-dioxide (SnO 2 ) nanoparticles irradiated by double laser pulses. As a result, the peak energy of the singly ionized tin ions was reduced from 9 to 3 keV.…”
mentioning
confidence: 99%
“…As a result, the peak energy of the singly ionized tin ions was reduced from 9 to 3 keV. 24 The optimized EUV productions need plasma with appropriate ion populations, which depend strongly on plasma density and temperature. The average charge state Z of an LPP is related to ion kinetic energy (E) and plasma temperature (T e ).…”
mentioning
confidence: 99%
“…We believe that the shape of the Sn target is crucial [8][9][10][11][12]. To realize this, a double-laser irradiation process is utilized in our system.…”
Section: Double-pulse Laser Irradiation When a Sn Droplet Target Is mentioning
confidence: 99%